Higher education expansion and social inequalities in sub-Saharan Africa: Conceptual and empirical perspectives - Yann Lebeau; Ibrahim O. Oanda (United Nations Research Institute for Social Development (UNRISD), 2020)
The development of higher education (HE) in sub-Saharan Africa has presented contradictory features and outcomes over the past two decades. On the one hand, the number of public and private HE institutions has increased in the present era of massification (where HE environments have reached almost universal access). This led to a diversification of academic programmes on offer, and enrolments surged to the point that sub-Saharan Africa experienced the fastest growth of all UNESCO world regions over the period. Yet on the other hand, gross enrolment rates (less than 10 percent on average in the region) remain by far the lowest and show slower progression than in other parts of the global South, as the rise in the number of institutions and in enrolment has not kept pace with population growth and increased social demand for higher education. These contradictions between dynamics typically associated with massified HE environments and features of highly elitist systems beg a closer examination of this process of expansion and diversification, and more specifically of how it has affected different socio-economic groups. Drawing on secondary data and policy material, and using three national contexts as case studies (Kenya, Nigeria and Senegal), the paper highlights how issues of inequalities and inequity in access to and participation in higher education were addressed by national policies in contexts of expansion and diversification. It then examines how the HE opportunities resulting from the expansion generated new inequalities at the levels of access to HE institutions and programmes, in student experience and in access to labour markets and social recognition. The case study perspective reveals how the relationship between growth and other dimensions of national HE developments are both context-contingent and shaped, or exacerbated by, international pressures. It allows a better understanding of the common challenges of African HE systems in terms of access "for whom?" "to what?" and "what for?" while avoiding excessive generalizations in conclusions and suggestions.
Keywords: 330; Access to higher education; inequalities; Kenya; massification; Nigeria; Senegal